Циклические особенности процессов слияний и поглощенийв мировой экономике - Курочкина, И.Г. (Культура народов Причерноморья, 2014)
В статье исследованы особенности и характерные черты волн слияний и поглощений, проанализированы мировые тенденции развития сделок слияний и поглощений, системы корпоративного контроля, механизмов государственного регулирования этих процессов. Также проанализирована динамика крупнейших рынков слияний и поглощений – США и Европы, что позволило сделать вывод об одинаковых чертах развития корпоративных рынков слияний и поглощений. Сделаны выводы о начале развития новой волны слияний и поглощений. У статті досліджені особливості і характерні риси хвиль злиттів і поглинань, проаналізовані світові тенденції розвитку угод злиттів і поглинань, системи корпоративного контролю, механізмів державного регулювання цих процесів. Також проаналізовано динаміку найбільших ринків злиттів і поглинань - США і Європи, що дозволило зробити висновок про однакові рисах розвитку корпоративних ринків злиттів і поглинань. Зроблено висновки про початок розвитку нової хвилі злиттів і поглинань. The article is devote explores the features and characteristics of the wave of mergers and acquisitions, analyzed global trends in mergers and acquisitions, corporate control mechanisms of state regulation of these processes. Also analyzed the dynamics of the largest M & A market - the US and Europe, which led to the conclusion of the same features of the development of corporate mergers and acquisitions market. The analysis showed that the world's leading US and European markets have the same dynamics and characteristics of corporate M & A market, which indicates a high level of transnationalization of the world economy and erase the division of international companies on American or European. It is concluded that the formation of the prerequisites start another wave of mergers and acquisitions, which is influenced by the depreciation of corporate assets due to the global financial crisis of 2008-2009., Which creates conditions for the purchase of companies with a market value below their real production or innovation and intellectual capacity.